Predictors of Quality of Life Improvement in Allergic Rhinitis Patients After Sublingual Immunotherapy. (June 2015) - Katotomichelakis, Michael; Riga, Maria; Tripsianis, Gregory; Balatsouras, Dimitrios; Kourousis, Christos; Danielides, Gerasimos; Giotakis, Evangelos; Danielides, Vassilios
Objectives: Sublingual immunotherapy (SLIT) has been described as a significant intervention in the treatment of allergic rhinitis (AR). However, factors that may predict treatment outcomes with respect to quality of life (QoL) results and mainly the role of olfactory function are still being underestimated. In this study, we investigated determinants that best predict treatment outcomes for QoL, exploring mainly the role of olfaction. Methods: One hundred forty-five patients following SLIT, 45 placebo-controls, and 48 healthy subjects were studied. Olfactory function was objectively evaluated using "Sniffin' Sticks" test pre- and post-cessation of SLIT. Three categories of validated QoL questionnaires were filled out by all subjects: questionnaire specific for olfaction (Questionnaire of Olfactory Deficits), questionnaires for assessing psychology (Beck Depression Inventory, Zung Depression Scale, State & Trait Anxiety Inventory), general Short Form-36 health survey. Results: Statistically significant improvement of olfactory function by 11.1% and of all QoL questionnaires results (all P < .001) was observed on final evaluation. Anosmia, asthma history, and the severity of symptoms—expressed by the Total Symptoms Score—were proven independent determinants of clinically significant improvement in patients' QoL. Conclusions: Several factors were found that may predict QoL outcomes in AR patients following SLIT.